Cultural Immersion as a Language Teaching Method - Uralov Islom Ural o’g’li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This thesis explores cultural immersion as a language teaching method, analyzing its effectiveness in fostering linguistic proficiency and cultural competence. Unlike traditional classroom-based approaches, cultural immersion provides learners with real-life exposure to the target language, enhancing communication skills, contextual understanding, and cultural awareness. The study examines various immersion strategies, compares them with other teaching methods, and discusses challenges such as adaptation difficulties and accessibility. Through a review of relevant literature and case studies, the thesis argues that cultural immersion is one of the most effective methods for second language acquisition.